2021
DOI: 10.1101/2021.01.26.21250409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genetic architecture of obsessive-compulsive disorder: alleles across the frequency spectrum contribute liability to OCD

Abstract: ObjectiveObsessive-compulsive disorder (OCD) is known to be substantially heritable; however, the contribution of common genetic variation across the allele frequency spectrum to this heritability remains uncertain. We use two new, homogenous cohorts to estimate heritability of OCD from common genetic variation and contrast results with prior studies.MethodsThe sample consisted of 2096 Swedish-born individuals diagnosed with OCD and 4609 controls, all genotyped for common genetic variants, specifically >400… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Compulsive symptoms rather than obsessive symptoms had higher SNP heritability and genetic correlations with OCD (Smit et al, 2019 ). Heritability for SNPs with a minor allele frequency between 0.1% and 5% for OCD is reported to be 0% (Davis et al, 2013 ); however, these results are not yet replicated (Mahjani et al, 2021 ). Given that twin- and SNP-based heritability estimates are in a similar range, particularly for adult OCD (van Grootheest, Cath, Beekman, & Boomsma, 2005 ), this suggests that common genetic variants account for a substantial portion of the variance for OCD (Davis et al, 2013 ).…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Compulsive symptoms rather than obsessive symptoms had higher SNP heritability and genetic correlations with OCD (Smit et al, 2019 ). Heritability for SNPs with a minor allele frequency between 0.1% and 5% for OCD is reported to be 0% (Davis et al, 2013 ); however, these results are not yet replicated (Mahjani et al, 2021 ). Given that twin- and SNP-based heritability estimates are in a similar range, particularly for adult OCD (van Grootheest, Cath, Beekman, & Boomsma, 2005 ), this suggests that common genetic variants account for a substantial portion of the variance for OCD (Davis et al, 2013 ).…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Modern genomic methods demonstrated that the genetic contribution to OCD is primarily polygenic, meaning that hundreds or thousands of genetic variants each contribute a very small amount to the overall genetic predisposition to OCD [50,53]. There is some evidence from copy number variants studies and wholeexome sequencing studies that rare variants exerting larger effects Fig.…”
Section: Key Concepts and Definitionsmentioning
confidence: 99%
“…All samples were genotyped using the Global Screening Array and analyzed for common genetic variation (B. Mahjani et al, 2021). All samples are currently going through wholeexome sequencing to detect rare structural variation and single nucleotide variation.…”
Section: Study Populationmentioning
confidence: 99%